Maternal behavior in provider of reproductive health education to early childhood - Yenti, Melisa; Permata, Inda Mustika; Mivtahurrahimah, Mivtahurrahimah (Intelektual Pustaka Media Utama, 2025)
Society often views sex education for early childhood as taboo, believing it is inappropriate for young children. However, early health education plays a crucial role in reducing the risk of sexual violence. In 2022, the Indonesian government recorded a high incidence of sexual violence, with 11.016 reported cases. This study examines the factors that influence maternal behavior in providing reproductive health education to early childhood in West Sumatra during 2021. This study uses a quantitative cross-sectional study method, the research conducted in May to October 2021 in West Sumatra. The study involved 257 mothers with children aged 3-6 years, selected through cluster sampling. We analyzed the data using univariate and bivariate analysis, employing the Chi-square method. The result shows that factors such as attitudes (0.029), exposure to information (<0.001), and family support (<0.001) significantly influence maternal behavior in providing reproductive health education. However, knowledge levels do not show a significant influence on maternal behavior. In addressing these findings, we recommend strengthening family support through family counseling training programs and increasing the availability and accessibility of information on reproductive health education.